SISTEM INFORMASI INVENTORY BARANG MENGGUNAKAN METODE WATERFALL - Fisa Wisnu Wijaya; Diana Lomban (Jurnal Informatika Teknologi dan Sains, 2022)
One of the computerized information systems is the website, usually in offline or online format. The transmission of information takes place through an online information system that can be accessed by anyone, from anywhere as long as there is an Internet connection. The aim of this study is to provide a solution by investigating various theories and observations related to the design of a web-based inventory information system. The application development approach that I use is the System Development Lifecycle (SDLC) approach which uses a waterfall-to-testing process model. The programming languages ??used are PHP and MySQL as the database. The expected outcome of the survey was the creation of an application that simplifies data processing, detects product availability earlier, and allows users to report product availability. products quickly and accurately.